S-Allylmercapro-N-Acetylcysteine Attenuates the Oxidation-Induced Lens Opacification and Retinal Pigment Epithelial Cell Death In Vitro - Naphtali Savion; Samia Dahamshi; Milana Morein; Shlomo Kotev-Emeth (MDPI AG, 2019)
The capacity of S-Allylmercapto-N-acetylcysteine (ASSNAC) to protect human retinal pigment epithelial (RPE) cells (line ARPE-19) and porcine lenses from oxidative stress was studied. Confluent ARPE-19 cultures were incubated with ASSNAC or N-acetyl-cysteine (NAC) followed by exposure to oxidants and glutathione level and cell survival were determined. Porcine lenses were incubated with ASSNAC and then exposed to H2O2 followed by lens opacity measurement and determination of glutathione (reduced (GSH) and oxidized (GSSG)) in isolated lens adhering epithelial cells (lens capsule) and fiber cells consisting the lens cortex and nucleus (lens core). In ARPE-19 cultures, ASSNAC (0.2 mM; 24 h) increased glutathione level by 2–2.5-fold with significantly higher increase in GSH compared to NAC treated cultures. Similarly, ex-vivo exposure of lenses to ASSNAC (1 mM) significantly reduced the GSSG level and prevented H2O2 (0.5 mM)-induced lens opacification. These results demonstrate that ASSNAC up-regulates glutathione level in RPE cells and protects them from oxidative stress-induced cell death as well as protects lenses from oxidative stress-induced opacity. Further validation of these results in animal models may suggest a potential use for ASSNAC as a protective therapy in retinal degenerative diseases as well as in attenuation of oxidative stress-induced lens opacity.